Determinants of female final year students pursing as an entrepreneur - Chan, Hong Yee (2023)
This research applied theory of planned behavior to determine the major dimensions which is education, entrepreneurial disposition, family support, family background and individual entrepreneur orientation that will affect the entrepreneurial intention of female final year student. The reasons that using theory of planned behavior is because there have some previous studies mentioned that this is the most appropriate theory used to determine intention.